Pathogenicity of Indigenous Entomopathogen Liquid Formulation to Paddy Bugs Nymphs (Leptocorisa acuta Thunberg) - Mulyani, Rahmawati Budi; Melhanah, Melhanah; Advianto, Petrayadi; Djaya, Adrianson A (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2022)
The purpose of this study was to determine the effectiveness of bio insecticide liquid formulations made from indigenous entomopathogens against paddy bugs nymphs. The study used a non-factorial Complete Randomized Design with 9 treatments and 1 control with five replications. The treatments studied consisted of E0: Control, E1: Beauveria sp Pky isolate + coconut water (CW), E2: Metarhizium sp isolate Jjt + AK, E3: Beauveria sp isolate Jts + CW, E4: Metarhizium sp isolate Lcc + CW, E5: Beauveria sp Pky isolate + shrimp shell extract (SSE), E6: Metarhizium sp isolate Jjt + SSE, E7: Beauveria sp isolate Jts + SSE, E8: Metarhizium sp isolate Lcc + SSE, E9: Synthetic insecticide b a Carbamate (Dharmabas 500 EC 2 ml L-1). The result showed that liquid bioinsecticide formulations were effective against mortality, infected nymphs and nymph death time. All entomopathogenic fungi isolates were able to cause infections in paddy bugs nymphs of 68% - 84%. Beauveria sp Pky isolate and Metarhizium sp isolate Jjt caused nymph mortality of 72% - 84% and the effectivity did not differ from insecticide b.a. Carbamate. Conidia viability of all entomopathogenic isolates in liquid media within 24 hours reached more than 80%. The fastest time to death of paddy bugs nymph occurred at 5.44 days ( Metarhizium sp. isolate) and 5.92 days (Beauveria sp. isolate) in coconut water media. Metarhizium sp. and Beauveria sp. in the medium of coconut water or shrimp shell extract has a very high potential to be developed as a bio insecticide, but it still needs to be further tested for its effectiveness in field conditions.Keywords: indigenous entomopathogen, coconut water, shrimp shell extract, paddy bugs nymph